Basic Principles of Wastewater Treatment - Von Sperling, Marcos (Biological Wastewater Treatment Series, 2007)
"Basic Principles of Wastewater Treatment is the second volume in the series Biological Wastewater Treatment, and focusses on the unit operations and processes associated with biological wastewater treatment. The major topics covered are: microbiology and ecology of wastewater treatment reaction kinetics and reactor hydraulics conversion of organic and inorganic matter sedimentation aeration The theory presented in this volume forms the basis upon which the other books of the series are built. About the series: The series is based on a highly acclaimed set of best selling textbooks. This international version is comprised by six textbooks giving a state-of-the-art presentation of the science and technology of biological wastewater treatment. Other titles in the series are: Volume 1: Wastewater Characteristics, Treatment and Disposal; Volume 3: Waste Stabilisation Ponds; Volume 4: Anaerobic Reactors; Volume 5: Activated Sludge and Aerobic Biofilm Reactors; Volume 6: Sludge Treatment and Disposal"